Evolution and coupled matching of ecosystem service supply and demand at different spatial scales in the Shandong Peninsula urban agglomeration, China - Shuwan Yan; Hao Chen; Quan Quan; Jian Liu (Ecological Indicators, 2023)
Ecosystem services are the environmental basis of human living and sustainable development, and the coupled matching of ecosystem service supply and demand (ESSD) plays an important role in socioeconomic and eco-environmental development. As one of the major regions supplying ecological products in China, the Shandong Peninsula urban agglomeration (SPUA) has unique geographical advantages and a strategic position. Based on high-resolution land-use and regional socioeconomic development data in SPUA, this study used value quantity assessment and an ecosystem service demand model to quantify ecosystem service supply (ESS) and ecosystem service demand (ESD) at both the city and county scale in 2000, 2010 and 2020. Meanwhile, the CA-Markov model was used to predict the potential land-use, the Moran index and Getis-Ord Gi* index were used to analyze spatial clusters of ESS and ESD, and a coupling coordination degree model and matching index were used to analyze the relationship between ESS and ESD. The results show that: (1) The most prominent land-use change in SPUA from 2000 to 2020 was the conversion of cropland to other land-use types; the process of land-use change was more intense from 2010 to 2020 than from 2000 to 2010; and the center of city activities might expand by 2030, which is related to the regional development plan. (2) The ESS was related to the regional natural conditions. Coastal regions or regions with abundant natural resources in SPUA had higher ESS, and the southwest region had lower ESS in SPUA. The ESS presented high–high clusters, low–low clusters and hot spots, and the cluster phenomena gradually diminished from 2000 to 2020. (3) The ESD was related to the regional location and economic development, with the southwest region of SPUA having a higher ESD than the northeast. The ESD presented low–low clusters, and Jinan and Qingdao had hot spots, which are the most developed cities in SPUA. (4) The study scale had impacts on coupled matching of ESSD. Coupled matching of ESSD was found to be unbalanced at the county scale from 2000 to 2020, but tended to be balanced at the city scale, which was related to resource management at different spatial scales. This study reveals the evolution and coupled matching of ESSD at different scales, which has important implications for the sustainable development of regional urban agglomerations.